ANALISIS KEPUASAN WAJIB PAJAK: PENDEKATAN TERHADAPPENGGUNAAN TEKNOLOGI INFORMASI DAN SELF ASSESSMENT - Purwito Kesdu AC (STIE AUB Surakarta, 2013)
The aim of this study is to investigate the influence of using Information technology and self assessment system to tax prayers’ Satisfaction. The Hypothesis which have been formulated in this research are: there is direct and indirect influence of using Information technology and self assessment system to tax prayer’s Satisfaction. The research is a survey to tax payers in Surakarta, Data have been collected with quesionaries as 100 respondents are processed with, validity and reliability test, the regression analysis, t test, F test and test of R2. Keyword: using Information technology, self assessment system, tax prayers Satisfaction.